Regional Integration and Poverty: A case study of Bolivia - Osvaldo Nina; Lykke E. Andersen (Institute for Advanced Development Studies (INESAD), 2004)
This paper investigates the impacts of regional integration processes on poverty in Bolivia. It first demonstrates that regional integration has stimulated a diversion of trade away from traditional US and EU markets towards countries of MERCOSUR and the Andean Community. At the same time, the composition of exports has changed from predominantly minerals towards slightly more elaborated goods, such as vegetable fats, food and beverages. The paper presents econometric analyses of the impact of imports, exports and FDI (by sector, and trade block) on individual labor incomes and household poverty status. The results show that higher exports generally tend to benefit the workers who work in the exporting sectors. However, this result only holds for export sectors that exploit some natural resource rents (mining, hydrocarbons, modern agriculture), and not for those which rely purely on low wages in order to be competitive (most manufacturing sectors). Imports typically have a negative effect on worker salaries, except the imports of capital goods, which do not compete with local production. This implies that the change towards more regional trade of goods with a smaller natural resource rent component is unlikely to contribute to a reduction in poverty. For exports and FDI to be helpful for reducing poverty, they would have to focus on sectors, which are labor intensive and at the same time exploit some natural resource rents. Sectors that might fulfill these criteria are modern agriculture and tourism.
Keywords: F15; 330; Regional integration; poverty; Bolivia